1993
DOI: 10.1029/93gl00865
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of VLBI data with the Ice‐3G Glacial Rebound Model

Abstract: Crustal motion predicted by the ICE‐3G glacial rebound model exhibits a pattern of tangential (horizontal) divergence away from the centres of uplift, which in North America and Europe are located around Hudson Bay and the Gulf of Bothnia. Tangential velocities reach peak magnitudes of 1–2 mm/yr, and must be included when predicting Very‐Long‐Baseline‐Interferometry (VLBI) baseline‐length change rates due to post‐glacial rebound. Out of 18 observed VLBI baselines examined 3 are situated such that their predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 6 publications
2
46
0
Order By: Relevance
“…Thus, the systematic pattern of tangential velocities radiating outward from the uplift centres can be difficult to separate from plate tectonic motion (James and Lambert, 1993;Argus et al, 1999). GPS offers the currently most cost-efficient method to tailor dense observation networks for continuous monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the systematic pattern of tangential velocities radiating outward from the uplift centres can be difficult to separate from plate tectonic motion (James and Lambert, 1993;Argus et al, 1999). GPS offers the currently most cost-efficient method to tailor dense observation networks for continuous monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Many space geodetic techniques have the sensitivity to recover horizontal deformation components due to post-glacial rebound (James and Lambert, 1993;Mitrovica et al, 1993;Argus et al, 1999;Campbell and Nothnagel, 2000;Haas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Our results based on ARC3+ANT4b indicate that the predicted deformation fields are very sensitive to the lower mantle viscosity (see also Mitrovica et al, 1994b). James and Lambert (1993) have predicted the crustal motions due to postglacial rebound, and suggested that horizontal motions are much sensitive to the mantle viscosity than radial motions. Our conclusion, however, indicates that spatial variations and amplitudes of both horizontal and vertical crustal motions are equally sensitive to the viscosity structure of the mantle.…”
Section: Discussionmentioning
confidence: 85%
“…There have been recent studies comparing VLBI measurements at northern latitude sites with the expected signals from post glacial rebound. Tushingham [1991] discusses the effects to be expected and Mitrovica et al [1993], James andLambert [1993], andMiirovica et al [1994] all report on the comparison of VLBI measurements with the signals both in the horizontal and vertical directions expected from post glacial rebound. All of these studies indicate that the precision in height rates of change or of baseline length rates of the change is not yet sufficient to make any definitive statements about the current accuracy of post glacial rebound models.…”
Section: Global Sea Level and Post Glacial Reboundmentioning
confidence: 99%